2017
DOI: 10.2105/ajph.2016.303576
|View full text |Cite
|
Sign up to set email alerts
|

Incarceration Rates and Traits of Sexual Minorities in the United States: National Inmate Survey, 2011–2012

Abstract: Objectives To report characteristics of sexual minority US inmates. Methods We drew our data from the National Inmate Survey, 2011–2012, a probability sample of inmates in US prisons and jails. We determined weighted proportions and odds ratios with 95% confidence intervals to estimate differences between sexual minority and heterosexual inmates. Results Sexual minorities (those who self-identify as lesbian, gay, or bisexual or report a same-sex sexual experience before arrival at the facility) were dispro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 16 publications
4
90
0
Order By: Relevance
“…An analysis of 2014 data from the Bureau of Justice Statistics reported that Black women had 1.6 to 4.1 times more likelihood of incarceration than White women (Carson, 2015). Sexual minorities are significantly overrepresented amid those who are incarcerated, comprising 42.1% of all incarcerated women (Meyer et al, 2017). Of transgender women, nearly one in five (19.3%) experienced incarceration, and 41.6% among these were transgender Women of Color (Reisner, Bailey, & Sevelius, 2014).…”
Section: Detention and Corrections: Juveniles Adults Re-entry And mentioning
confidence: 99%
“…An analysis of 2014 data from the Bureau of Justice Statistics reported that Black women had 1.6 to 4.1 times more likelihood of incarceration than White women (Carson, 2015). Sexual minorities are significantly overrepresented amid those who are incarcerated, comprising 42.1% of all incarcerated women (Meyer et al, 2017). Of transgender women, nearly one in five (19.3%) experienced incarceration, and 41.6% among these were transgender Women of Color (Reisner, Bailey, & Sevelius, 2014).…”
Section: Detention and Corrections: Juveniles Adults Re-entry And mentioning
confidence: 99%
“…One of the proposed mechanisms by which same sex sexual behavior is associated with deleterious health outcomes is increased exposure to interpersonal stress and stressful life events. The minority stress model posits that members of highly stigmatized groups experience chronically high levels of stress resulting from discrimination (e.g., overt, internalized), disproportionate exposure to stressful life events (e.g., violent victimization, criminal justice involvement), and low socioeconomic status [20][21][22]. The burden of these stressors can lead to negative health outcomes, such as higher mortality rates, as well as the use of negative coping behaviors like substance use [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The minority stress model posits that members of highly stigmatized groups experience chronically high levels of stress resulting from discrimination (e.g., overt, internalized), disproportionate exposure to stressful life events (e.g., violent victimization, criminal justice involvement), and low socioeconomic status [20][21][22]. The burden of these stressors can lead to negative health outcomes, such as higher mortality rates, as well as the use of negative coping behaviors like substance use [20][21][22]. It is imperative to acknowledge the complex nature of health disparities that span multi-level domains of influence and extend the focus beyond the individual to value the importance of social and structural factors [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations